2014
DOI: 10.1016/j.ntt.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlational analysis reveals no association between MPP+ and the severity of striatal dopaminergic damage following MPTP treatment in BXD mouse strains

Abstract: 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) is a pro-neurotoxicant that must be metabolized to 1-methyl-4-phenylpyridinium (MPP(+)) and taken up into striatal dopaminergic neurons to produce neurodegeneration. Recently, we showed wide genetic variability in MPTP-associated neuronal damage in a panel of recombinant inbred mouse strains. Here we examined the amount of MPP(+) produced in the striatum in the same strains of inbred BXD mice. This allowed us to determine if the differences in the dopaminergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…By using systems genetics, we showed that the extent of MPP+ production was quantitatively unrelated to the extent of DA loss in the striatum and showing once again that MPTP neurotoxicity is highly complex and determined by multiple factors (Jones et al, 2014). There is evidence showing the possible involvement of other enzymes such as mitochondrial cytochrome P450 2D6 (CYP2D6) in addition to monoamine oxidase B (MAOB) in the metabolism of MPTP to MPP+ (Bajpai et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…By using systems genetics, we showed that the extent of MPP+ production was quantitatively unrelated to the extent of DA loss in the striatum and showing once again that MPTP neurotoxicity is highly complex and determined by multiple factors (Jones et al, 2014). There is evidence showing the possible involvement of other enzymes such as mitochondrial cytochrome P450 2D6 (CYP2D6) in addition to monoamine oxidase B (MAOB) in the metabolism of MPTP to MPP+ (Bajpai et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…Knowing that the production of MPP+ is crucial to neurological destruction, we asked the question as to whether the extent of DA loss in the striatum is directly related to the amount of MPP+ produced. Comparing the mean loss of DA with the mean production of MPP+ the correlation was -0.15 and not significant at 7 degrees of freedom ( Jones et al, 2014b ). This illustrates one of the advantages of forward genetic analysis using a systems perspective.…”
Section: Introductionmentioning
confidence: 93%